2007
DOI: 10.1007/bf03165763
|View full text |Cite
|
Sign up to set email alerts
|

Papel de genes adipogénicos y termogénicos en la resistencia o susceptibilidad al desarrollo de obesidad inducida por la dieta en rata

Abstract: The aim of the present work was to assess whether changes in adipose tissue gene expression related with adipogenesis and/or thermogenesis could be involved in the mechanism conferring susceptibility or resistance to develop obesity in high-fat fed outbreed rats. For this purpose, male Wistar rats were fed with standard laboratory diet (control group) or high fat diet. After 15 days, two groups of rats with significant differences on body weight gain in response to the high fat diet were characterized and iden… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 43 publications
(57 reference statements)
1
6
0
Order By: Relevance
“…It is worth noting that MnTBAP caused a slight but significant increase in the average adipocyte diameter in NC-fed animals (Figure 4a, b). Next, we examined the effect of MnTBAP on adipogenesis and fat uptake in eWAT and found that consistent with prior reports (14, 15), HFD enhanced adipogenesis in eWAT as evidenced by the significant (p<0.05) increase in mRNA expression of key adipogenic genes such as PPARγ and aP2 (Figure 4c), an induction that was prevented with MnTBAP. Interestingly, these changes in adipogenesis were not observed in iWAT (Supplementary Figure 3), suggesting a depot-specific effects of HFD and MnTBAP.…”
Section: Resultssupporting
confidence: 86%
“…It is worth noting that MnTBAP caused a slight but significant increase in the average adipocyte diameter in NC-fed animals (Figure 4a, b). Next, we examined the effect of MnTBAP on adipogenesis and fat uptake in eWAT and found that consistent with prior reports (14, 15), HFD enhanced adipogenesis in eWAT as evidenced by the significant (p<0.05) increase in mRNA expression of key adipogenic genes such as PPARγ and aP2 (Figure 4c), an induction that was prevented with MnTBAP. Interestingly, these changes in adipogenesis were not observed in iWAT (Supplementary Figure 3), suggesting a depot-specific effects of HFD and MnTBAP.…”
Section: Resultssupporting
confidence: 86%
“…49 The down-regulation of RARγ expression prior the onset of adipogenesis is an essential molecular signature of several in vitro pre-adipocyte differentiation models [48][49][50] while in vivo, an inverse correlation between RARγ expression and adiposity has been demonstrated. 48,65 Moreover, RARγ agonism inhibits the expression of the pro-adipogenic nuclear receptor PPARγ and thereby blocks the adipogenic signals emanating from this receptor. 46,51,66,67 Our observation that the addition of an RARγ agonist prior to adipogenesis induction blocks PPARγ-stimulated adipogenesis of LNCaP cells is consistent with these findings.…”
Section: Analysis Of Adipogenic Differentiationmentioning
confidence: 99%
“…Compared with their OR counterparts, OP rats show a more adverse metabolic risk profile as well as lower energy expenditure on a HFD [9,10], and a proadipogenic expression profile [11-13]. In addition, OP rats also have lower relative fat oxidation and fat oxidation enzyme expression [14-17].…”
Section: Introductionmentioning
confidence: 99%